La cooperación eficaz vulnera el derecho a la defensa de los imputados, en la etapa de evaluación y preparatoria de juicio en el Ecuador. - Macías, Gustavo R. (2022)
The Effective Cooperation in a literally new special investigation technique, since within the previous Criminal Code or within the Code of Criminal Procedure it was not mentioned, but with the entry into force of the Comprehensive Criminal Organic Code in its article 491 it is included, in order to investigate certain specific crimes that are committed in the country, but, for this special investigation technique to be valid, an effective collaborator is required, as its name indicates, who must provide truly effective information in exchange for a minimum penalty. . This figure in Ecuador has been well seen, since it has allowed the dismantling of several criminal organizations thanks to the help of the effective collaborator who, by releasing all the information, is deserving of a minimum penalty, but what about the co-processors? Do they have the same opportunities as the collaborator? Can they also benefit from a sentence reduction? We are going to develop these questions in this research work, since the general objective is to demonstrate the existence of the violation of the right of the co-defendants to have adequate time and means for their investigation, defense in cases of effective cooperation.